2018
DOI: 10.1159/000487407
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis of Single Large Hepatocellular Carcinoma Was Distinct from Barcelona Clinic Liver Cancer Stage A or B: The Role of Albumin-Bilirubin Grade

Abstract: Background/Aims: Whether single large hepatocellular carcinoma (SLHCC) is classified as Barcelona Clinic Liver Cancer (BCLC) stage A or B is still controversial. We aimed to compare the clinical manifestations, treatment modalities, and prognoses among patients with SLHCC and those in BCLC stage A and B. Methods: We enrolled 2,285 treatment-naive hepatocellular carcinoma (HCC) patients with BCLC stage A or B from October 2007 to December 2015. Factors in terms of prognoses were analyzed by multivariate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…The disease outcomes of HCC patients post-liver resection is partly affected by the existing liver physiological status. In accordance with previous studies 10,11,25,26 , we determined that ALBI grade could in uence the OS of the total cohort and tumor size ≤7 cm subgroup. The patients who had an ALBI grade 1 presented a better survival time compared to those had an ALBI grade 2 in the total cohort.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The disease outcomes of HCC patients post-liver resection is partly affected by the existing liver physiological status. In accordance with previous studies 10,11,25,26 , we determined that ALBI grade could in uence the OS of the total cohort and tumor size ≤7 cm subgroup. The patients who had an ALBI grade 1 presented a better survival time compared to those had an ALBI grade 2 in the total cohort.…”
Section: Discussionsupporting
confidence: 74%
“…We observed that patients whose tumors were > 7 cm presented a lower albumin level, greater blood loss, and a higher proportion of serum AFP ≥ 400 ng/ml and poor differentiation than patients with tumor size ≤ 7 cm. AFP is regarded as an important prognostic indicator for HCC undergoing liver resection 18,21 . A high level of preoperative AFP often indicates poor survival time after surgery 22 .…”
Section: Discussionmentioning
confidence: 99%
“…ALBI score = (log10 bilirubin × 0.66) + (albumin × −0.085). ALBI grades were defined as grade 1 (score ≤ -2.60), grade 2 (score > -2.60 and ≤ -1.39), and grade 3 (score > -1.39) (12). APRI was calculated as [(AST value/ULN)/platelet count (10 9 /L)] × 100 (13).…”
Section: Definitionsmentioning
confidence: 99%
“…(2) In contrast, a recent case-control study using the Taiwan National Health Insurance Research Database conducted by Shao et al reported that proton pump inhibitor use might increase the risk of hepatocellular carcinoma in patients without hepatitis B infection or hepatitis C infection (odds ratio, 2.86; 95% confidence interval, 2.69-3.04). (3) Because of conflicting results in these observational studies, some points should be discussed. First, at least 90% of patients with hepatocellular carcinoma in Taiwan are associated with chronic hepatitis B infection or chronic hepatitis C infection.…”
Section: To the Editormentioning
confidence: 99%
“…Because the majority (>80%) of HCC patients in Taiwan and East Asia have an active ongoing or resolved viral hepatitis, our study might provide more clinical implications for patients who bear a higher risk of developing HCC. (3) Regarding the nonviral etiology of HCC, Lai conducted a cohort study using the Taiwan NHI database, and it showed that incidences of HCC were similar between PPI users and non-PPI users after excluding alcohol-related disease, cirrhosis, hepatitis B infection, hepatitis C infection, other chronic hepatitis, and diabetes mellitus. (4) Furthermore, another recent meta-analysis of five observational studies demonstrated that PPI use was not associated with an increased risk of HCC.…”
Section: Replymentioning
confidence: 99%